Faktor-faktor Determinan yang Mempengaruhi Penerimaan Diri Pasien Stroke dengan Keterbatasan Gerak - Nurhalimah Nurhalimah; Pipin Farida Yosefina; Omi Haryati (Jurnal Keperawatan, 2018)
Stroke cases in Indonesia are increasing rapidly, stroke sufferers are not only old but also young. Riskesdas (2013) described the highest Stroke prevalence in North Sulawesi (10.8 ‰), followed by DI Yogyakarta (10.3 ‰), Bangka Belitung and DKI Jakarta, 9.7 per mile respectively. Post-stroke patients have an impact on the lives of patients, because individuals cannot do many things and achieve the best things in their lives, unable to fulfill their development tasks, unable to carry out activities to meet their needs and also interfere with the community in their environment. The purpose of the study was to get a description of the determinant factors of self-acceptance of patients with limited mobility due to stroke. With Research Design: Descriptive analytic with cross sectional approach, Population of patients who have a stroke. The sample in this study were: post-stroke patients who experienced limited mobility. Research Location: in the area of ​​Cipayung Subdistrict, period with data collection techniques: Disseminating research instruments, Analysis of data: Univariate, Bivariate and Multivariate Analysis The results of this study concluded that patients with good spiritual levels contributed 5 times better than stroke patients with self spiritual low